Periodicals and Nation-Building: The Public Sphere, Modernity, and Modernism in Modern Review and Visva Bharati Quarterly - Singh, Akansha (Text Matters: A Journal of Literature, Theory and Culture, 2023)
The paper analyzes selections from Modern Review and Visva Bharati Quarterly, to study the complex act of nation-building taking place in India during the first half of the twentieth century. Through these periodicals, it discusses three interconnected occurrences that contributed to the envisioning of new India: firstly, the construction of a politically aware public sphere through nationalistic sentiments and anti-imperial internationalism; secondly, India’s localization of modernity as oscillating between the colonial subjects’ reactionary modernity and the colonially administered modernity of domination; and thirdly, the emergence of a modernism that was more immersed in restructuring social and political systems of power than being restricted to formal and aesthetic novelty. Thus, drawing on writings published in Modern Review and Visva Bharati Quarterly, the paper assesses the degree to which the two periodicals realized the identity of new India.